Refugees welcome? Introducing a new dataset on anti-refugee violence in Germany, 2014-2015 - David Benček; Julia Strasheim (Kiel Institute for the World Economy (IfW), 2016)
The recent rise of xenophobic attacks against refugees in Germany has sparked both political and scholarly debates on the drivers, dynamics, and consequences of right-wing violence. Thus far, a lack of systematic data collection and data processing has inhibited the quantitative analysis to help explain this social phenomenon. This paper introduces a new georeferenced event dataset on anti-refugee violence and social unrest in Germany in 2014 and 2015 based on a public chronicle. Our dataset includes information of 1645 events of four different types of right-wing violence and social unrest: demonstrations, assault, arson attacks, and miscellaneous attacks against refugee housing. After discussing how the dataset was constructed, we offer a descriptive analysis of patterns of right-wing violence and unrest in Germany in 2014 and 2015. We conclude by outlining preliminary ideas on how the dataset can be used in future research.
Keywords: C80; D74; J15; 330; right-wing extremist violence; georeferenced event data; refugees